Onychomycosis and its Homoeopathic Management (Homoeopathy for All, 2026)
Onychomycosis, a common fungal infection of the nails, predominantly caused by dermatophytes such as Trichophyton rubrum, affects a significant portion of the global population. From a homoeopathic standpoint, this condition is not merely a localized fungal issue but a manifestation of internal systemic dyscrasia. Homoeopathy approaches onychomycosis through individualized treatment, focusing on the patient’s constitution, miasmatic tendencies, and underlying susceptibility. This integrative approach aims not only to address the local infection but also to correct the internal imbalance, thereby preventing recurrence and promoting holistic health.
Keywords: Trichophyton rubrum; fungal issue; onychomycosis; (NDMs)